First Grade Elementary School Students’ Reflective Thinking Skills in Thematic Learning. - Rahayu Setyowati; Suprapti (UIN Raden Mas Said Surakarta, 2022)
This study elucidates the reflective thinking ability as one of the higher-order thinking skills (HOTS) in thematic learning of grade I students. It also identifies factors affecting students’ reflective thinking ability at MI Al-Islam Kartasura. This study is nested in a qualitative method with a descriptive case study. Involving students of class IA and a class teacher, data collection was carried out using non-test techniques in the form of observation, interviews, and documentation. The results indicated that students could answer the